Swyer syndrome with heterotopic adrenal cortical tissue in streak gonads: A rare case and review of literature - Manu Goyal; Shuchita Batra; Pratibha Singh; Shashank Shekhar; Poonam Elhence (Journal of Human Reproductive Sciences, 2019)
Swyer syndrome is a 46 XY pure gonadal dysgenesis. Affected individuals are phenotypically female with external female genitalia, hypoplastic Mullerian structures, and the presence of streak gonads. Gonadectomy is indicated due to increased risk of development of malignancy in streak gonads. We hereby report a case of 15-year-old patient with Swyer syndrome who underwent laparoscopic gonadectomy. Histopathological examination showed streak gonads with the presence of accessory adrenal cortical tissue. The patient was put on hormonal replacement therapy postsurgery. Heterotopic adrenal rest may be an incidental finding in normal ovary and testis. Its presence in streak gonads has never been reported, and we propose a theory of increased risk of gonadal and adrenal tumors, possibly because of mutations in disorders of sex differentiation.